Replaceable Jejunal Feeding Tubes in Severely Ill Children. (23rd January 2017) - Pang, Tabea; Sesia, Sergio B.; Holland-Cunz, Stefan; Mayr, Johannes
Abstract : Long-term enteral nutrition in chronically ill, malnourished children represents a clinical challenge if adequate feeding via nasogastric or gastrostomy tubes fails. We evaluated the usefulness and complications of a new type of surgical jejunostomy that allows for easier positioning and replacement of the jejunal feeding tube in children. We surgically inserted replaceable jejunal feeding tubes (RJFT) connected to a guide thread which exited through a separate tiny opening of the abdominal wall. In a retrospective case series, we assessed the effectiveness and complications of this technique in severely ill children suffering from malnutrition and complex disorders. Three surgical complications occurred, and these were addressed by reoperation. Four children died from their severe chronic disorders within the study period. The RJFT permitted continuous enteral feeding and facilitated easy replacement of the tube. After the postoperative period, jejunal feeding by RJFT resulted in adequate weight gain. This feeding access represents an option for children in whom sufficient enteral nutrition by nasogastric tubes or gastrostomy proved impossible. Further studies are required to investigate the safety and effectiveness of this surgical technique in a larger case series.